Botulinum toxin as a treatment for short bowel syndrome in rats - Marques,Isabela Cristina de Souza (2019)
Abstract Purpose: The denervation of the intestine with benzalkonium chloride (BAC) reduces mortality and improves weight gain in rats with short bowel syndrome (SBS). Nevertheless, translating these promising findings from bench to bedside is not feasible because BAC promotes peritonitis and irreversible denervation which may be followed by an uncontrolled dilatation of the viscera. The use of botulinum toxin (BT) instead of BAC to achieve the denervation of the remaining small intestine in SBS could be an interesting option because it leads to a mild and transient denervation of the intestine. Methods: Here we evaluated the effects of the ileal denervation with BT in rats with SBS by verifying the body weight variation and intestinal morphological parameters. Four groups with 6 animals each were submitted to enterectomy with an ileal injection of saline (group E) or BT (group EBT). Control groups were submitted to simulated surgery with an ileal injection of BT (group BT) or saline (group C - control). Results: We observed that the treatment of the remaining ileum with BT completely reversed the weight loss associated to extensive small bowel resection. Conclusion: This may provide a new promising approach to the surgical treatment of SBS.